To compare the efficacy of Gabapentin with Paracetamol for Preemptive Analgesia in children undergoing Tonsillectomy. - Anum Zeb, Muhammad Muazzam Butt, Aqeel Ahmad, Rifah Zia, Abaid-Ur-Rehman, Dawood Ahmad Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare the mean time for first rescue analgesia after preemptive gabapentin versus paracetamol for pain control after tonsillectomy in children. Method: This random controlled trial was conducted by Anesthesia team in ENT OT in Jinnah Hospital, Lahore from January 1, 2018 to June 30, 2018. After taking informed consent, 60 patients fulfilling the selection criteria were recruited and after obtaining demographic information, two groups were formed using lottery method Group G and Group P each having 30 patients. Patients were given oral Paracetamol 20 mg/kg and oral Gabapentin 10 mg/kg 120 minutes before induction of anesthesia in Group P and Group G respectively. Post-operatively, patients’ pain was monitored with VAS after every 30 minutes. When VAS exceeded 3, it marked the demand of first post-operative rescue analgesia was given and time was noted. Injection Ketorolac 0.5mg/kg was given as rescue analgesia. Mean time of first rescue analgesia was compared in between 2 groups via SPSS 19 Results: There were no significant differences for variables such as age and BMI in between two groups. The main result of study is that mean time for first rescue analgesia in group G and group P found to be 468.00± 57.14 & 377.00±51.47 minutes respectively. The calculated p-value was P < 0.0001 proving significant difference in duration for first analgesia in between two groups. Conclusion: There is significant difference in mean time for first rescue analgesia after preemptive gabapentin versus paracetamol for pain control after tonsillectomy in children. Keywords: Preemptive Analgesia, Gabapentine, Paracetamol, Post-operative pain control